2010
DOI: 10.1673/031.010.5301
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Attraction of the Larval Parasitoid,Hyposoter horticola, to Plants Infested with Eggs of the Host Butterfly,Melitaea cinxia

Abstract: Parasitoids locate inconspicuous hosts in a heterogeneous habitat using plant volatiles, some of which are induced by the hosts. Hyposoter horticola Gravenhost (Hymenoptera: Ichneumonidae) is a parasitoid of the Glanville fritillary butterfly Melitaea cinxia L. (Lepidoptera: Nymphalidae). Melitaea cinxia lays eggs in clusters on leaves of Plantago lanceolata L. (Lamiales: Plantaginaceae) and Veronica spicata L. (Lamiales: Plantaginaceae). The parasitoid oviposits into host larvae that have not yet hatched from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
1
10
1
Order By: Relevance
“…We found that they retained IGs as pupae, which has been shown in other herbivores adapted to IGs (Bowers & Puttick, 1986). ), and the two specialist parasitoids of M. cinxia larvae are more attracted to hosts on V. spicata than to hosts on P. lanceolata (van Nouhuys & Hanski, 2004;Castelo et al, 2010). Catalpol is the more toxic and (Puttick & Bowers, 1988;Bowers & Puttick, 1989;Bowers, 1991), and catalpol has been shown to have a negative effect on some parasitoids (Nieminen et al, 2003;Singer & Stireman, 2003;Laurentz et al, 2012).…”
Section: Host Food Plantsupporting
confidence: 66%
See 1 more Smart Citation
“…We found that they retained IGs as pupae, which has been shown in other herbivores adapted to IGs (Bowers & Puttick, 1986). ), and the two specialist parasitoids of M. cinxia larvae are more attracted to hosts on V. spicata than to hosts on P. lanceolata (van Nouhuys & Hanski, 2004;Castelo et al, 2010). Catalpol is the more toxic and (Puttick & Bowers, 1988;Bowers & Puttick, 1989;Bowers, 1991), and catalpol has been shown to have a negative effect on some parasitoids (Nieminen et al, 2003;Singer & Stireman, 2003;Laurentz et al, 2012).…”
Section: Host Food Plantsupporting
confidence: 66%
“…Plantago lanceolata and V. spicata have different volatile emissions (JH Reudler, D Mofikoya, JK Holopainen & S van Nouhuys, unpubl. ), and the two specialist parasitoids of M. cinxia larvae are more attracted to hosts on V. spicata than to hosts on P. lanceolata (van Nouhuys & Hanski, 2004;Castelo et al, 2010). We found no direct effect of plant species on whether a pupa became parasitised by P. apum in the field, where the attractiveness of the plant and the accessibility of the host were part of the experiment.…”
Section: Host Food Plantcontrasting
confidence: 52%
“…A foraging hyperparasitoid must first of all find M. cinxia caterpillar nests parasitized by H. horticola. Herbivory by M. cinxia causes the host plant to release volatile odors that lead H. horticola to their hosts (Castelo et al, 2010;Pinto-Zevallos et al, 2013). Such volatiles can also be attractive to hyperparasitoids (Zhu et al, 2014).…”
Section: Statistical Modelsmentioning
confidence: 99%
“…However, because of the difference in experimental design between the experiments with P. lanceolata and V. spicata that gave significantly different results, we cannot conclude with significance that effects on the two hosts were different, although this is likely. Correspondingly, and potentially through the same mechanism of induced plant response, V. spicata becomes attractive to the specialist parasitoid wasp Hyposoter horticola after M. cinxia eggs are laid on it, but P. lanceolata does not (Castelo et al 2010).…”
Section: Discussionmentioning
confidence: 99%